Faktor-Faktor Yang Mempengaruhi terhadap Efisiensi Pada Industri Perbankan Di Indonesia - Subri, Ahadi; Kusuma, Indra Wijaya ([Yogyakarta] : Universitas Gadjah Mada, 2011)
The objective of this research is to examine Capital Adequacy Ratio (CAR), Return on Assets (ROA), Loan to Assets (LTA), Number of Branches, Size and Low Cost Deposits (LCD) to take effect toward Efficiency in Indonesianâs Banking Industry. The research consisted of 14 Indonesianâs conventional banking with IDR.10.000 billion or more assets from 2002 to 2008. This research adopts a two-stage approach, Data Envelopment Analysis Model (DEA Model) and regression analysis, to investigate bank efficiency and efficiency effect. The result of this research show that ROA affects positively significant toward efficiency, LTA affects negatively significant toward efficiency at 10% level. CAR, Number of branches, Size and LCD are not affect toward efficiency. In this research, ROA is the most important factor that affecting toward efficiency in Indonesiaâs Banking Industry.